2021
DOI: 10.1093/infdis/jiab241
|View full text |Cite
|
Sign up to set email alerts
|

Incidences and Determinants of Functional Cure During Entecavir or Tenofovir Disoproxil Fumarate for Chronic Hepatitis B

Abstract: Background Long-term incidences and baseline determinants of functional cure (HBsAg seroclearance) during entecavir (ETV) or tenofovir disoproxil fumarate (TDF) treatment are incompletely understood. Methods This is an international multicenter cohort study of treatment-naïve chronic hepatitis B (CHB) patients who initiated on ETV or TDF without baseline malignancy. Patients were observed for HBsAg seroclearance until death o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…A large multinational multicenter long-term ETV/TDF therapy cohort study in 4769 patients demonstrated a 10-year HBsAg loss rate of 2.1% and an annual incidence of only 0.22% [40].…”
Section: Ultimate Goal Of Hbsag Loss Rarely Achievedmentioning
confidence: 99%
“…A large multinational multicenter long-term ETV/TDF therapy cohort study in 4769 patients demonstrated a 10-year HBsAg loss rate of 2.1% and an annual incidence of only 0.22% [40].…”
Section: Ultimate Goal Of Hbsag Loss Rarely Achievedmentioning
confidence: 99%
“…11 This estimation is supported by a most recent large international multicenter cohort study in 4769 patients with CHB, which showed a 10-year cumulative HBsAg loss rate of only 2% with a steady annual incidence of 0.2% (0.17%-0.28%) during 26,614 person-years of ETV/TDF therapy. 12 Indeed, indefinite long-term or even life-long Nuc therapy is required to achieve HBsAg loss, a desirable but unrealistic ultimate goal of "functional cure." This strategy has been the mainstream recommendation in the existing guidelines of all major liver association.…”
Section: Current Status Of Antiviral Therapy In Chronic Hbv Infectionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] It has been proposed that immune restoration during Nuc therapy and/or HBV reactivation elicited immune response may facilitate further HBsAg decline toward HBsAg loss. 19,32 A recent study of Nuc therapy in patients with HBV DNA <2000 IU/ml showed a 10-year HBsAg loss rate of only 1.26%, 12 12-44 times lower than that in untreated inactive carriers with HBV DNA <2000 IU/ml. 1,2,33,34 These findings strongly suggest that unnecessary Nuc therapy or retreatment may deprive the patients of HBsAg loss.…”
Section: High Hbsag Loss Rate Justifies Finite Nuc Therapy As An " Ac...mentioning
confidence: 99%
“…It is difficult to achieve the goal of HBsAg seroclearance with standard antiviral treatments. Functional cure occurs at an average annual rate of 0.22% in CHB patients during first-line oral NAs antiviral treatment ( 42 ). PEG-IFN treatment can acquire an average HBsAg clearance annual rate of 3% ( 43 45 ), 5-year cumulative rate of 14% and 10-year cumulative rate of 32% ( 46 ) in CHB patients.…”
Section: Immune Mechanisms Of Current Drugs and Emerging Therapies Ta...mentioning
confidence: 99%